GAMBARAN PENERAPAN DAN KELENGKAPAN PENGISIAN REKAM MEDIS ELEKTRONIK RAWAT JALAN DI RUMAH SAKIT TK.II UDAYANA DENPASAR - Suriawan, I Gde Agus Hendra; Devhy, Ni Luh Putu; Aditya, Made Wahyu (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
Complete medical record files can facilitate other health workers in providing patient care or treatment, and can be used as, a useful source of information for hospital management in determining the evaluation and development of health aservices. The impact of incomplete medical records is delays in the process of filing insurance claims and delays in the orderly administration process. The purpose of this study was to determine the completeness of filling out the Outpatient Electronic Medical Record at Tk.II Udayana Hospital Denpasar. The research method used is quantitative descriptive with a sample of 95 electronic medical records from July to September 2022 using the simple random samplingOmethod. The resultsashowed that 95 (100%) filled out identification completeness and 0 (0%) incomplete, 92 (96.8%) important report filling completeness and 3 (3.2%) incomplete filling, 69 (72.6%) authentication filling completeness) and 26 (27.4%) incomplete, 71 (74.7%) complete correct documentation and 24 (25.3%) incomplete. It can be concluded from the four analyses, the highest completeness of filling out outpatient RME at Tk. II Udayana Hospital Denpasar is found in important identification and reports. Based on the research above, the researchers suggest that hospitals should conduct socialization regarding the completeness of filling in RME to all health workers who are responsible for filling out electronic medical Records.